Revision of Iphione Kinberg, 1856 (Annelida, Aphroditiformia, Iphionidae) - Salazar-Vallejo, Sergio I.; Piotrowski, Christina N.; Paulay, Gustav (Zootaxa, 2024)
The only revision of Iphione was made by Pettibone in 1986, who recognized four species including two newly described in that work: I. muricata (Savigny in Lamarck, 1818) (type species), I. ovata Kinberg, 1856, I. treadwelli Pettibone, 1986, and I. henshawi Pettibone, 1986. She included I. fimbriata de Quatrefages, 1866, I. glabra de Quatrefages, 1866, and I. fustis Hoagland, 1920 within I. muricata, and I. spinosa Kinberg, 1856 and I. hirotai Izuka, 1912 in I. ovata. Three other species were later added to the genus: I. reticulata Amoureux, Rullier & Fishelson, 1978 from the Red Sea, I. coriolis Hanley & Burke, 1991 from the Coral Sea, and I. malifera Piotrowski, 2014 from the Philippines. A recent contribution showed that I. ovata ranges from the Red Sea to the Eastern Pacific and includes I. spinosa and I. reticulata. Our objectives were to revise the genus, evaluating all species and describing new ones by assessing the relevance of morphological features, assisted in part with COI sequence data. We studied the morphology of type and non-type material from 18 institutions and sequenced 52 specimens representing 11 species. We found that the size and position of eyes, the size relationships between cephalic appendages, and the number of rows of macrotubercles in elytra vary with body size. The most relevant diagnostic features for species delineation, confirmed by genetic species delineation, are the type and size relationships of macrotubercles, the presence of fimbriae, the development of the basal tubercle of dorsal cirrophores, the type of neurochaetae (falcate versus acicular), and their tips (uni- vs bidentate; or simple vs hooded). We clarified the type species of the genus as I. ovata, and recognized 17 species, nine previously described and eight new. Our main results include: 1) the restriction of I. muricata; 2) the reinstatement of I. fimbriata including I. fustis; 3) redescriptions of I. coriolis, I. henshawi and I. treadwelli; and 4) the description of eight new species: I. ankeri sp. nov. from Guam, I. corbari sp. nov. from the Saya de Malha Bank, I. harrisae sp. nov. from French Polynesia, I. hourdezi sp. nov. from New Caledonia, I. hyndmani sp. nov. from Hong Kong, I. readi sp. nov. from the Red Sea (including many earlier records of I. muricata), I. richeri sp. nov. from New Caledonia, and I. wilsoni sp. nov. from Australia. Descriptions the eight newly described species include only one based upon a single specimen. Keys are included for the genera in the family, and species of Iphione.